If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15y + -8 = 42 Reorder the terms: -8 + 15y = 42 Solving -8 + 15y = 42 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 15y = 42 + 8 Combine like terms: -8 + 8 = 0 0 + 15y = 42 + 8 15y = 42 + 8 Combine like terms: 42 + 8 = 50 15y = 50 Divide each side by '15'. y = 3.333333333 Simplifying y = 3.333333333
| 6x+5/3=4x+1/2+5x/6 | | 3=(5x-7)/x | | 2(x+5)/3=6x-5 | | 100*y=3.7041 | | x/9+6=-4 | | 1/9+4/9 | | 200=x(y) | | 10x-6=7x-3 | | x/7+8=-6 | | 15(x)=200 | | (5100/85+51-6)(61+64-124) | | 11=-5(4x+2)+21x | | (5100/85+51-6)-(61/64-124) | | 5/18-1/9 | | (8-u)(5u+9)=0 | | -1/3+1/6-1/9+1/12 | | (5100/85+51-6)(61/64-124) | | -5x/32-5x/32= | | z-3z=6z-6-z | | 1/3-1/6+1/9-1/12 | | 4/15-1/6 | | 8/13-2/13 | | x/2-1-x/7+4 | | (8x+3)(x^2-6x+2)=0 | | 4(5a+2)-5(3a+1)=2(a-1) | | y=-2x^2-4x+6 | | -9x/18+3x/18+3x/18= | | 7x+4=7(x+4) | | -x+2=23 | | 6(7x+3)+7=42x+25 | | 0.70+0.20(140)=0.35(144) | | 9m-4=-18 |